2010
DOI: 10.1086/649894
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Immune Activity, but Not Innate Immune Responsiveness, Covaries with Mass and Environment in Nestling House Wrens (Troglodytes aedon)

Abstract: Immunological measures are increasingly being applied to ecological and evolutionary studies of wild vertebrates, yet frequently it is not clear how condition and environmental factors correlate with various immune parameters. We used mixed-model ANOVA to examine the effects of several measures of condition (both morphological and physiological) and environmental factors on two measures of immune responsiveness in nestling house wrens (Troglodytes aedon L.) to test the hypothesis that nestlings in good conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 52 publications
2
32
2
Order By: Relevance
“…Additionally, Whiteman et al (2006) found that ectoparasite abundance on the Galapagos Hawk (Buteo galapagoensis) was negatively correlated with natural antibody titers, as measured by the hemolysis-hemagglutination assay. The lack of correlation between constitutive innate immunity and condition indices observed in this study is consistent with previous studies in birds (Palacios et al, 2009;Forsman et al, 2010), which suggest that the innate branch of the immune system is less sensitive to body condition than adaptive immunity. Additionally, anthropogenic food availability to urban birds is well known (Chamberlain et al, 2009), which might suggest that the birds measured here were not energetically limited, resulting in a minimal trade-off with immune function.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, Whiteman et al (2006) found that ectoparasite abundance on the Galapagos Hawk (Buteo galapagoensis) was negatively correlated with natural antibody titers, as measured by the hemolysis-hemagglutination assay. The lack of correlation between constitutive innate immunity and condition indices observed in this study is consistent with previous studies in birds (Palacios et al, 2009;Forsman et al, 2010), which suggest that the innate branch of the immune system is less sensitive to body condition than adaptive immunity. Additionally, anthropogenic food availability to urban birds is well known (Chamberlain et al, 2009), which might suggest that the birds measured here were not energetically limited, resulting in a minimal trade-off with immune function.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, the assay measures different humoral and cellular components of constitutive innate immunity, which represents an organism's first defense against invading pathogens (Matson et al, 2005). Microbicidal assays have been used to study differences in constitutive innate immunity among vertebrate species (Matson et al, 2006a, b) and under different environmental conditions (Allen et al, 2009;Zimmerman et al, 2010), physiologic conditions (Forsman et al, 2010), and infection profiles (Wilcoxen et al, 2010b;Beechler, pers. comm.…”
Section: Introductionmentioning
confidence: 99%
“…These common results in males could be interpreted on the light of common components in the innate and adaptive axes of the immune system (Forsman et al 2010;Vinkler et al 2010). In fact, some studies have shown that the PHA swelling response is an integration of both specific and induced immunity and also of constitutive and nonspecific immunity (Martin et al 2006a;Salaberria et al 2013).…”
Section: Discussionmentioning
confidence: 82%
“…A food-restriction study in nestling sand martins showed that trade-offs between growth and phytohemagglutinin (PHA) skin-swelling response (which involves both induced innate and adaptive cell-mediated immune components; Martin et al 2006) occurred when resources were experimentally limited (Brzęk and Konarzewski 2007). Several correlational studies of young birds showed a positive relationship between body mass or condition and magnitude of PHA skin-swelling response (Saino et al 1997;Soler et al 1999;Alonso-Alvarez and Tella 2001;Hoi-Leitner et al 2001;Chin et al 2005;Snoeijs et al 2005;Martin et al 2006;MartĂ­n-Vivaldi et al 2006;Forsman et al 2010). However, in some studies, a positive correlation was not observed when young birds were well fed, indicating a threshold for the resource dependence of the PHA response (AlonsoAlvarez and Tella 2001; Chin et al 2005;Snoeijs et al 2005;MartĂ­n-Vivaldi et al 2006).…”
Section: Introductionmentioning
confidence: 99%